Money balances, economic activities and selective capital controls in Malaysia - Mad, Che Ani (Faculty of Business, Bond University, 2005)
This paper reports results of a test of money demand and supply as predicted by recent studies applied to small economies with greater openness to external factors.These results suggest that the short- and long-run money balances are determined by both the interest rate policies as well as the price levels in the economy. With open conditions generally prevailing in our tested small economy, increases in interest rates attract portfolio funds, which helped to spur asset price bubble to build up.When the economy came under strain as a result, the bubble bursts as happened at the time of the Asian financial crisis, which led to a severe currency crisis that lasted for about 18 months, causing severe economic downturns thereafter. The findings may be taken to mean that control of short-run portfolio flow is critical in a more open small economy.